Effect of addition of organic matter on bacterial population dynamics of soil in potato and corn crops - García Ventocilla, David (2011)
The effect of organic fertilization on soil bacterial populations in potato and corn crops during the crop season 2008-2009 at four sites in the Mantaro Valley locations: INIA Santa Ana (Huancayo), the EEA El Mantaro (Jauja), Vista Alegre and Huayao (both in Chupaca). In these places were set up experimental plots of potato (Solanum tuberosum L. var. Canchan) and corn (Zea maize L. Var. Cusco enhanced) under organic manure (cattle, sheep, guinea pig), chemical fertilizer and no fertilizer at all (control) . To do this we used the techniques of electrophoresis Denaturing Gradient Gel (DGGE) with amplification of the region from 968 to 1401 of 16S rDNA. The results show that the variability of bacterial populations in soil is directly affected by crop type but not by the type of fertilization and the effect of the latter is variable for each experimental area and culture found only in the experimental area of Chupaca - Corn segregation of treatments with organic fertilization of chemical treatments. We have also found that the variation of the microbial communities did not suffer significant variations in soils with maize similarity coefficients obtained for all treatments above 80% while for the treatments in potato crops that rate was only 60%.